Taxpayer Compliance In The Green Era: The Relationship Between The Automatic Exchange Of Information Systems And The Green Economy - Celine Winona Duha; Rolyana Ferinia; Grace Orlyn Sitompul (Jurnal Ekonomi, 2024)
The nation's development depends on public participation in the political system, including paying taxes. Taxpayer compliance with tax payments is still an issue, and numerous instances of tax evasion and delinquent behavior exist. The government needs tax revenue to support green economy projects aimed at tackling climate change and promoting sustainability. Ensuring people pay their taxes is crucial for funding these programs and achieving the country's environmental goals. This study explores the relationship between taxpayer compliance with tax payments sin Indonesia and understanding of automated data exchange networks and the green economy. In this study, 100 respondents in Balikpapan Tengah, East Kalimantan, were given questionnaires, which were used to collect data using quantitative methodology and correlational design. The data was processed and examined using SmartPLS. The findings of the analysis show that the AEoI System significantly improves people's compliance in paying taxes. Furthermore, the green economy contributes to increased taxpayer compliance. The adoption of the green economy also benefits from a greater understanding of the automated information exchange process. The study's findings suggest that adopting automated information sharing and the green economy may impact taxpayer compliance with filing taxes. The government can use these two techniques to enhance tax compliance and base its policies on this conclusion